2007
DOI: 10.1007/s10592-007-9414-z
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting genetic structuring between colonies of the World’s smallest penguin, Eudyptula minor (Aves: Spheniscidae)

Abstract: The Little Penguin, Eudyptula minor, is a seabird that nests in colonies throughout New Zealand and southern Australia. Individuals from different colonies in southeast Australia differ significantly in morphology and ecology, suggesting that some genetic structuring may exist among colonies. In contrast, the marking of individuals with flipper bands has revealed some, albeit infrequent, movement between colonies. To determine the extent of genetic structuring, we tested the null hypothesis of substantial gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 71 publications
2
45
1
Order By: Relevance
“…In band‐rumped storm petrels Oceanodroma castro sympatric seasonal populations from two of the archipelagos studied (the Azores and Cape Verde) have ceased to exchange genes, providing the first example of sympatric speciation by allochrony in a tetrapod (Monteiro and Furness 1998, Friesen et al 2007b). In penguins, sea surface temperatures seem to be primarily related to differences in breeding phenology which seems to have an effect on the diversification among populations of the little penguin Eudyptula minor (Overeem et al 2008) and speciation of the rockhopper penguin Eudyptes chrysocome (Jouventin et al 2006). Furthermore, rockhopper penguins are separated by the sub‐tropical convergence, which also separates the Brazilian and Patagonian populations of the South American tern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In band‐rumped storm petrels Oceanodroma castro sympatric seasonal populations from two of the archipelagos studied (the Azores and Cape Verde) have ceased to exchange genes, providing the first example of sympatric speciation by allochrony in a tetrapod (Monteiro and Furness 1998, Friesen et al 2007b). In penguins, sea surface temperatures seem to be primarily related to differences in breeding phenology which seems to have an effect on the diversification among populations of the little penguin Eudyptula minor (Overeem et al 2008) and speciation of the rockhopper penguin Eudyptes chrysocome (Jouventin et al 2006). Furthermore, rockhopper penguins are separated by the sub‐tropical convergence, which also separates the Brazilian and Patagonian populations of the South American tern.…”
Section: Discussionmentioning
confidence: 99%
“…However, in seabirds non‐physical barriers and behavioural processes such as non‐breeding distribution and phylopatry, also play an important role in promoting genetic differentiation (reviewed by Friesen et al 2007a). More recently, isolation by time has also been described as a key mechanism preventing gene flow in seabirds (Friesen et al 2007b, Overeem et al 2008).…”
mentioning
confidence: 99%
“…These are inherited from both parents and have higher rates of substitution relative to mitochondrial DNA, making them more sensitive to weak or recent population structure. Most of these studies have found high genetic diversity and a lack of genetic differentiation between colonies (Adélie, Roeder et al 2001;Magellanic, Spheniscus magellanicus, Bouzat et al 2009;Humboldt, Spheniscus humboldti, Schlosser et al 2009), though breaks in genetic connectivity with distance have also been recorded (little penguin, Eudyptula minor, Overeem et al 2008;yellow-eyed penguin, Megadyptes antipodes, Boessenkool et al 2009). For chinstrap penguins, there has not been a region-wide investigation using microsatellite markers.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting the genetic structure of colonial bird populations is not straightforward, as it depends both on contemporary ecological and/or behavioural features (such as the degree of natal philoptary and breeding dispersal, population size, and mating system) and on phylogeographic history (Tiedemann et al 2004, Matthiopoulos et al 2005, Milot et al 2008, Overeem et al 2008). For instance, stronger or weaker genetic structure than expected from ecological data (Milot et al 2008) or from population history (Boessenkool et al 2009) has been reported in seabirds.…”
mentioning
confidence: 99%